2016
DOI: 10.1007/s00221-016-4793-3
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-oculomotor skills related to the visual demands of sporting environments

Abstract: The aim of this study was to assess the visuo-oculomotor skills of gaze orientation in selected sport activities relative to visual demands of the sporting environment. Both temporal and spatial demands of the sporting environment were investigated: The latency and accuracy of horizontal saccades and the gain of the horizontal smooth pursuit of the sporting environment were investigated in 16 fencers, 19 tennis players, 12 gymnasts, 9 swimmers and 18 sedentary participants. For the saccade test, two sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…In the same vein, a recent study 14 showed that when reinforcement is contingent upon specific saccadic latencies in a choice paradigm, humans learned to adjust their SRT distributions depending on the reinforcement contingencies in force: the relative proportions of short- and long-latency saccades matched the relative proportions of reinforcement obtained for each class of latencies. Eye movement studies outside the laboratory with sportsmen 19 or video-gamers 20 demonstrated similar temporal-learning abilities. It is worth noting that low-level target properties, such as luminance, have been shown to compete with internal factors based on previous experience in controlling saccade reaction time 9 , 21 23 .…”
Section: Introductionmentioning
confidence: 78%
“…In the same vein, a recent study 14 showed that when reinforcement is contingent upon specific saccadic latencies in a choice paradigm, humans learned to adjust their SRT distributions depending on the reinforcement contingencies in force: the relative proportions of short- and long-latency saccades matched the relative proportions of reinforcement obtained for each class of latencies. Eye movement studies outside the laboratory with sportsmen 19 or video-gamers 20 demonstrated similar temporal-learning abilities. It is worth noting that low-level target properties, such as luminance, have been shown to compete with internal factors based on previous experience in controlling saccade reaction time 9 , 21 23 .…”
Section: Introductionmentioning
confidence: 78%
“…For example, Land and McLeod (2000) examined cricket batsmen's eye movements and found that, for the most successful batsmen, eye fixation occurred in a period of 100-200 ms and followed a faster onset of saccade latencies (time from target presentation to eye movement onset). Other studies have also shown a significant decrease in saccadic onset latency in elite athletes (Ceyte et al, 2017;Piras et al, 2010). Thus, short saccade onset latency appears to be related to a superior visuo-oculomotor system in elite athletes.…”
Section: Introductionmentioning
confidence: 89%
“…Previous coincidence anticipation research with elite sport participants have sometimes yielded ambiguous results, due to several methodological concerns and uncertainty regarding the underlying mechanisms involved. Regarding the uncertainty in underlying mechanisms, we suggest that if elite athletes have gained superior visuo-oculomotor skills through long-term training (Ceyte et al, 2017;Land, 2009), they should show different eye movements (compared with nonathletes) during coincident-timing tasks. Methodological concerns include uncertainty as to whether the coincident-timing stimulus paradigm is a sufficiently difficult laboratory task for elite athletes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, shorter latencies demanded by urgency (e.g., Montagnini & Chelazzi, 2005) or longer latencies due to reduced visual benefits of saccades (e.g., Harwood et al, 2008;Madelain, Krauzlis, & Wallman, 2005) have been reported, revealing the ability to learn when to saccade. This temporal learning is incidentally thought to be at play outside the laboratory with sportsmen (Ceyte, Lion, Caudron, Perrin, & Gauchard, 2017) or video-gamers (Chisholm & Kingstone, 2015). Recently, Vullings and Madelain (2018) have investigated how the temporal organization of the environment constrains the temporal allocation of saccades.…”
Section: Introductionmentioning
confidence: 99%